Transparency of Subject and Gamification of Reality: The Case of the System-Medical Fiction Great Doctor Ling Ran. - Xin, Wang; Keller, Jeffrey; Pan with, Siyun; Yang, Renren (Chinese Literature & Thought Today, 2024)
Since 2018, "system-medical fiction" (xitong yiliao wen) has become a popular genre of web novel, which is situated at the intersection of media and reality. Through the setting of a "system," this genre links the professional careers of physicians with video games, reflecting the dual trends of "media becoming reality" and "reality becoming media." In turn, the system lying between the human subject and the surrounding social realities leads to the increasing "transparency of the subject" and "gamification of reality." In this context, the human subject faces the risk of being deprived of a gratification channel, while social realities also face the possibility of being completely overshadowed by the system.